Desain Arithmetic Logic Unit 8bit untuk Central Processing Unit 8bit - Ega Dewa Iswantoro; Mochammad Hannats Hanafi Ichsan; Wijaya Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Arithmetic Logic Unit or commonly called ALU is an important part of the Central Processing Unit or commonly called CPU. ALU generally has a function to perform arithmetic and logic calculations. The 8bit Arithmetic Logic Unit for Central Processing Unit-8bit also has the same functionality to process mathematical and logic data. Some functions contained in the ALU are the ADD, unmarked sums (ADDU), subtraction (SUB), unmarked subtraction (SUBU) and some OR, XOR and AND logic functions. In the 8bit Arithmetic logic unit design for central processing unit 8bit using IC adder, AND, OR, NOT and multiplexer. For the main input use 2 switches I / 0 and 3 input input switches for multiplexers, and menggukan LED media as outputan. This circuit is designed to use 8 twin sets which each series represents 1 bit. The design of this circuit uses 5volt power as its main power source. In the test part of Arithmetic logic unit 8bit performance will be tested by comparing the output output of ALU and manual count with 3 different input on each function.